2020
DOI: 10.1155/2020/7510120
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Immune Genes in Bladder Urothelial Carcinoma

Abstract: Background. The aim of this study is to identify possible prognostic-related immune genes in bladder urothelial carcinoma and to try to predict the prognosis of bladder urothelial carcinoma based on these genes. Methods. The Cancer Genome Atlas (TCGA) expression profile data and corresponding clinical traits were obtained. Differential gene analysis was performed using R software. Reactome was used to analyze the pathway of immune gene participation. The differentially expressed transcription factors and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Studies found that IRGs play critical regulatory roles in immune responses, including the following: regulation of differentiation and development of bone marrow hematopoietic stem cells; regulation of the development, differentiation, and activation of immune cells; and participation in the activation of autophagy and inflammatory processes [ 27 ]. Studies showed that IRGs predict survival and outcomes for various tumors, and they are potential targets for tumor therapy [ 5 , 7 , 8 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that IRGs play critical regulatory roles in immune responses, including the following: regulation of differentiation and development of bone marrow hematopoietic stem cells; regulation of the development, differentiation, and activation of immune cells; and participation in the activation of autophagy and inflammatory processes [ 27 ]. Studies showed that IRGs predict survival and outcomes for various tumors, and they are potential targets for tumor therapy [ 5 , 7 , 8 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Cao et al 30 using TCGA‐BLCA data set found four survival‐related immune cells and 24 hub genes, four of which were related to overall survival. Recently, there were many papers published using only TCGA‐BLCA data set to analyse the tumour‐infiltrating immune cells and prognostic genes related to the microenvironment of bladder cancer 31‐37 . Additionally, Song et al 38 using TCGA‐BLCA data set analysed immune‐related long non‐coding RNA signature for muscle‐invasive bladder cancer; Li et al 39 using GES13507 data set analysed tumour microenvironment and found three immune‐related prognostic genes for bladder cancer; Luo et al 40 and Qiu et al 41 using TCGA‐BLCA as training cohort and http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE13507 as validation cohort constructed six and seven immune‐related genes prognostic signature, separately; Tian et al 42 using TCGA‐BLCA cohort and four GEO data sets (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE13507, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE48075, http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE31684 and http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE32894) identified a prognostic signature based on six immune‐related genes.…”
Section: Discussionmentioning
confidence: 99%